Can the Chinese Cultural Attraction Become an Icon of Tourism Cultural Heritage? (A Case in China Village, Manado) - Towoliu, Benny Irwan; Permana, Dimas Ero; Sangari, Fonny (Jurnal Ilmiah Peuradeun, 2020)
The purpose of this study was to analyze the residents’ perception towards the Chinese cultural attraction as an icon of cultural heritage tourism in Manado city. Manado is a predominantly Christian community and dominated by indigenous Minahasa tribes. But, now the city is populated by various inhabitants such as Sangir, Gorontalo, Maluku, and even foreign immigrants such as China and Arab migrating since the Dutch colonial era. Of the various communities that exist, practically only the Chinese community that still maintains its rituals amid strong advances in the tourism industry, this cultural practice can become an icon for cultural tourism. However, can the cultural ritual be accepted as an icon of Manado cultural tourism? This research was in the form of a descriptive qualitative approach. The instruments of data collection were questionnaires and field observations. Questionnaires were distributed to 325 respondents spread in Manado. Empirical results showed that every ritual attraction of Chinese Culture had always been awaited and an interesting spectacle for the people of Manado since the people of Chinese descent domiciled in Manado City. These findings could also provide recommendations for policymakers in setting annual tourist agendas as well as providing legal certainty for this region of Chinatown with various attractions as a cultural heritage area.